PRINSIP-PRINSIP KUALITI KE ARAH MELAHIRKAN USAHAWAN MUSLIM YANG BERJAYA - Basir, Siti Arni (Jurnal Syariah, 2019)
Since entrepreneurship involves business risks, business profit and loss have been given attention by entrepreneurs. It is important for Muslim entrepreneurs to apply quality principles to sustain their business. This is to ensure that consumer interest is protected. This article focuses on quality principles Muslim entrepreneurs must practice to be successful in their business. This article aims to discuss the definition of an entrepreneur, entrepreneurship theories and the vital role of entrepreneurs in developing countries. It will also discuss market freedom, managing greediness and self-reliance, establishing business network and the economic struggle matters that must be adhered by Muslim entrepreneurs.